2009
DOI: 10.1007/s12583-009-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Unusual mantle mineral group from chromitite orebody Cr-11 in Luobusa ophiolite of Yarlung-Zangbo suture zone, Tibet

Abstract: A wide variety of unusual mantle has been reported from podiform chromitite orebodies Cr-31 and Cr-74 in the Luobusa (罗布莎) ophiolite, Tibet. A detailed investigation of chromitite orebody Cr-11, located in the Kangjinla (康金拉) district at the eastern end of the ophiolite, has revealed many of the same minerals, including diamond, moissanite, and some native elements, alloys, oxides, sulphides, silicates, carbonates, and tungstates. This orebody is particularly rich in diamonds, with over 1 000 grains recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 5 publications
3
50
0
Order By: Relevance
“…Diamonds and serpentine pseudomorphs after octahedral olivine were discovered many years ago in podiform chromitite of the Luobusa ophiolite (IGCAGS, 1981;Yang et al, 1981) and have been confirmed by subsequent workers (Hu, 1999;Bai et al, 2000a;Robinson et al, 2004;Yang et al, 2007Yang et al, , 2008Yang et al, , 2009. Similar UHP and highly reduced minerals have also been found recently in both the chromitites and peridotites of Luobusa, including coesite (possibly pseudomorphing stishovite) (Yang et al, 2007), kyanite, a diamond inclusion in Os-Ir alloy (Yang et al, 2007), diamond in peridotite , inclusions of silicon spinel in Os-Ir alloy (Bai et al, 2005), and reduced phases such as moissanite, wüstite, native elements and base-metal alloys (Hu, 1999;Bai et al, 2000bBai et al, , 2006Robinson et al, 2004;Fang et al, 2009;Shi et al, 2009;Xu et al, 2009). Diamond and moissanite have now been confirmed as insitu phases in the chromitites .…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Diamonds and serpentine pseudomorphs after octahedral olivine were discovered many years ago in podiform chromitite of the Luobusa ophiolite (IGCAGS, 1981;Yang et al, 1981) and have been confirmed by subsequent workers (Hu, 1999;Bai et al, 2000a;Robinson et al, 2004;Yang et al, 2007Yang et al, , 2008Yang et al, , 2009. Similar UHP and highly reduced minerals have also been found recently in both the chromitites and peridotites of Luobusa, including coesite (possibly pseudomorphing stishovite) (Yang et al, 2007), kyanite, a diamond inclusion in Os-Ir alloy (Yang et al, 2007), diamond in peridotite , inclusions of silicon spinel in Os-Ir alloy (Bai et al, 2005), and reduced phases such as moissanite, wüstite, native elements and base-metal alloys (Hu, 1999;Bai et al, 2000bBai et al, , 2006Robinson et al, 2004;Fang et al, 2009;Shi et al, 2009;Xu et al, 2009). Diamond and moissanite have now been confirmed as insitu phases in the chromitites .…”
Section: Introductionsupporting
confidence: 64%
“…Abundant diamonds and moissanite have been recovered from mineral separates of the chromitites (Hu, 1999;Bai et al, 2001;Robinson et al, 2004;Xu et al, 2009). Diamonds and moissanite also occur in-situ as inclusion in chromite grains ).…”
Section: Origin Of the Chromitites In The Kangjinla Peridotitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The material that makes up the subject of both ref. 8 and this article has been extracted from massive chromite ore 93 of the Luobusa ophiolite, located on the collisional boundary between Asia and India (13,14).…”
mentioning
confidence: 99%
“…These studies include: major and trace elemental and/or isotopic compositions of different textural chromitites and their host peridotites (e.g., [1][2][3][4][5][6][7][8]), and unusual ultrahigh-pressure (UHP), highly reduced and crustally derived minerals found either in situ or as separates in the chromitites and peridotites (e.g., [9][10][11][12][13][14][15][16][17][18][19][20][21]). [42]), and the distribution of magmatism on the Lhasa terrane (modified from Chung et al [43]).…”
Section: Introductionmentioning
confidence: 99%